Impact of virtual reality with or without hypnosis before oocyte retrieval: A randomised study - Céline Pirard; Pascale Laurent; Christine Wyns; Maria-Grazia Giudice; Christine Watremez; Mona Momeni; Fabienne Roelants (Complementary Therapies in Medicine)
Objective of the study: Anxiety can affect pregnancy rate following an in-vitro-fertilisation procedure. Hypnosis reduces emotional distress associated with medical procedures. Virtual reality (VR) is an immersive 3D experience, created using a visual headset and headphones. The goal of this study was to evaluate the effect of VR session with and without hypnosis before sedation for oocyte retrieval (OR) on anxiety levels and on pregnancy rate. Methods: After written informed consent, 342 women scheduled for OR under sedation were randomised in this double-blinded study (NCT03064061). A Visual Analogue Scale for anxiety (VAS) and a Spielberger State-Trait Anxiety Inventory (STAI) questionnaire before (baseline) and after VR session, and at hospital discharge were administered. VRD Group (n = 178) received a VR session (goal of distraction) and VRH group (n = 164) received the same VR session with hypnosis focused on slowing respiratory rhythm and suggestions of reusing the technique later as needed (AQUA Oncomfort/HypnoVR ™). The primary endpoint was ongoing pregnancy at 12 weeks. Mann Whitney, Wilcoxon signed rank test and Chi-square tests were used; p value < 0.05 considered significant. Results: Although anxiety scores decreased from baseline in both VRD and VRH groups (p < 0.001 baseline vs post VR session and baseline vs hospital discharge), there was no difference between them. Nor was there a difference in pregnancy rate (18,6 % VRD group vs 22,5 % VRH group). Conclusion: Although both VRD and VRH sessions before sedation for OR significantly reduced women's anxiety, the type of suggestions used during the hypnosis VR session did not influence the pregnancy rate.